FORMULASI GEL HAND SANITIZER EKSTRAK DAUN PEGAGAN (Centella asiatica) DAN AKTIVITASNYA TERHADAPStaphylococcus aureus - Maulita Saraswati; Gigih Kenanga Sari; Wahyu Purwanjani (Universitas An Nuur, 2022)
Background: Indonesia is a tropical country that has very abundant biodiversity and has various potentials for health. One of these biodiversities is pegagan leaves (Centella asiatica). Pegagan (Centella asiatica) is one of the plants that contains antibacterial substances, including flavonoids, saponins, tannins, phenols and steroids. Prevention of the spread of bacteria can be done by washing hands with soap and clean running water. Along with the development of science and technology, cleaning hands does not have to use water and soap but can use antiseptic hand gel (hand sanitizer) to kill microorganisms on the surface of the skin. Purpose: to determine whether the gotu kola leaf extract hand sanitizer gel preparation has antibacterial activity against Staphylococcus aureus Method: Extraction by maceration of pegagan leaf extract (Centella asiatica) using 96% ethanol solvent. After obtaining a thick extract, then enter it into the formulation to make a hand sanitizer gel preparation which is then tested on Staphylococcus aureus bacteria using the disc diffusion method. Results: The results of this study showed that the hand sanitizer gel with pegagan extract (Centella asiatica) showed an inhibitory effect on bacterial growth with an inhibitory value of 15.4 mm in formulation 3 with a pegagan extract concentration of 60%. Conclusion: Hand sanitizer gel from pegagan extract (Centella asiatica) has antibacterial activity against Staphylococcus aureus